Menelusuri Ibdal dalam Syarah Ibnu Aqil: Perubahan Bunyi dan Keindahan Bahasa (Argopuro: Jurnal Ilmu Bahasa, 2025)
This study aims to examine the phenomenon of ibdal (الإبدال) in the Syarah Ibnu Aqil by Ibnu Aqil al-Misri, with a focus on aspects of phonetic changes and their contribution to the beauty of the Arabic language. This research employs a qualitative approach using the content analysis method. Data were obtained through an in-depth review of Syarah Ibnu Aqil, particularly sections containing both explicit and implicit instances of ibdal. The analysis was conducted descriptively to identify ibdal patterns, positions of phonetic changes within words, and the aesthetic functions that emerge. The results of the study show that the phenomenon of ibdal in Syarah Ibnu Aqil is highly diverse, including patterns such as the substitution of t with ط, n with m, waw with ya’, and ibdal within the context of dialectal variation. Each form of ibdal plays both linguistic and aesthetic roles, ranging from facilitating pronunciation and adjusting morphological structures to enhancing phonetic beauty in poetry. Furthermore, the phenomenon of ibdal demonstrates a close relationship between phonological rules and the aesthetic sensibility of the Arabic language. Therefore, understanding ibdal is essential in the teaching of both classical and modern Arabic. This study is expected to contribute to the development of Arabic linguistic studies and open new avenues for further research on ibdal in other texts.